SLEEP QUALITY AND AFFECTING FACTORS AMONG ELDERLY LIVING IN A NURSING HOME AT EAST NUSA TENGGARA INDONESIA - Asyifa Robiatul Adawiyah; Kusharisupeni Djokosujono; Jumiati Lelu Sanga (Indonesian Journal of Public Health Nutrition, 2022)
Sleep is one of the processes that greatly affects aging, It essential for mental, physical, and maintenance of physical health. Kupang East Nusa Tenggara, Indonesia, a research study in a nursing home of the elderly experience have a bad quality of sleep. This study aimed to analyze the sleep quality and the factors affecting, among old age living in a nursing home at East Nusa Tenggara Indonesia. The research design was cross-sectional with primary data on 103 elderly living in nursing homes. There was a relationship between age, gender, marital status, spouse, education background, have a chronic diseases, living arrangement, anxiety, and depression with sleep quality (p<0.05). The correlation showed that there was a strong and positive patterned relationship (<0.05) between the total anxiety score and the total sleep quality score (r=0.608) and the total depression score with the total sleep quality score (r=0.561) meaning that the higher of the elderly felt anxiety and depression worsened for the quality of sleep. Old age who lives alone are more susceptible to stress or depression resulting from unconvenient environment where they live. High levels of anxiety and depression in the elderly are associated with poorer sleep quality.